2016
DOI: 10.1021/acs.jpclett.6b01237
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanism of Iron(III) Oxide Nucleation

Abstract: A molecular understanding of the formation of solid phases from solution would be beneficial for various scientific fields. However, nucleation pathways are still not fully understood, whereby the case of iron (oxyhydr)oxides poses a prime example. We show that in the prenucleation regime, thermodynamically stable solute species up to a few nanometers in size are observed, which meet the definition of prenucleation clusters. Nucleation then is not governed by a critical size, but rather by the dynamics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
121
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(135 citation statements)
references
References 38 publications
13
121
0
1
Order By: Relevance
“…[27] Here, the titrationc urve ( Figure 1) can be subdivided into at least two distinctr egionst hat can be regardeda sp re-and postnucle-ation stages. [25] During the prenucleation stage, only ligand exchange and olation bridging processes take place and lead to the formation of ad ynamic population of olation PNCs. [25,27] Phase separationo ccurs on upwards bending of the curve, with significant deviation from the initially linear profile (fine dottedl ine in Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] Here, the titrationc urve ( Figure 1) can be subdivided into at least two distinctr egionst hat can be regardeda sp re-and postnucle-ation stages. [25] During the prenucleation stage, only ligand exchange and olation bridging processes take place and lead to the formation of ad ynamic population of olation PNCs. [25,27] Phase separationo ccurs on upwards bending of the curve, with significant deviation from the initially linear profile (fine dottedl ine in Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently,i th as been shownt hat the early stages of iron(III) oxide formation at room temperaturea nd low drivingf orce for phases eparation-that is, at low degrees of supersaturation, which are apparent from significant durationso fp renucleation stateso fm etastable equilibrium on slow mixing of solutionsmechanistically proceeda ccording to the notions of the socalled prenucleation cluster (PNC) pathway. [25,26] In the case of iron (oxyhydr)oxides,t hermodynamically stable PNCs are dynamico lation polymers that qualify as solutes and are part of the homogeneous,m etastable solution. On phase separation, the formation of oxo bridgesi nt he clusters renders them less dynamicd ue to the stronger bonds bridgingthe iron(III) centers.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic contributions of cluster species are recognized for several metals, metal oxides and semiconductors such as CdS, iridium, iron (oxyhydr) oxides, silver and titanium oxide particles . Conventionally addressed as ‘nanoclusters’, particles smaller than 2 nm typically exhibit atomic level rearrangements and distinct physical properties in relation to larger solid particles .…”
Section: On the Nature Of Materials Precursorsmentioning
confidence: 99%
“…[1] Nevertheless, despite the broad interest and great efforts from many disciplines, the detailed mechanism of iron oxide nucleation and phase transformation, and the roles of various evolved species remain obscure. Recently, it was shown that at low driving force for phase separation (i.e., low pH and iron concentration) olation polymers can be regarded as stable pre-nucleation clusters (PNCs), where the onset of oxolation within the PNCs triggers a decrease in their dynamics, [2] which is the chemical basis of a phase separation event according to the notions of the PNC pathway. [3] The mechanism is consistent with the chemistry of iron oxides that has been extensively studied for decades, where the hydrolysis of iron salts in aqueous solutions produces very small colloidal particles (also termed as polycations, clusters, or primary particles) with a size of 1-4 nm.…”
mentioning
confidence: 99%
“…The AIO-PCDA cluster has a well-defined core-shell structure with the chelation of Fe by gauche PCDA chains, and the co-existence of Fe 2+ and Fe 3+ was also identified. Thermal gravimetric analysis (TGA, Figure S14 Figure S15) further detected the largest species to be Fe 9 O 3 -(OH) 16 ·6 H 2 O:(PCDA) 2 , and with it, we constructed the structure of an AIO-PCDA cluster, as shown in Figure S16. The AIO core has an approximate size of 1.1 nm (Figure S17), which is apparently smaller than the ligand-free AIO cluster (ca.…”
mentioning
confidence: 99%